2008
DOI: 10.1016/j.tiv.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity evaluation of diesel exhaust particles on human eosinophilic cell

Abstract: Abstract:Diesel exhaust particles (DEPs), comprised mainly of particles less than 2.5μm (PM2.5) in aerodynamic diameter, have been assumed to enhance the response of asthma to allergen inhalation. Although eosinophilic infiltration is remarkable in the event of bronchial asthma induced by DEPs, the precise mechanisms leading to eosinophilia are unknown. To examine the effect of DEPs on eosinophils, we measured the cytokine products and activity of nuclear factor -kappa B (NF-κB) after addition of the proteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Consistent with this, we and others have previously demonstrated that DEP exposure induces and/or aggravates airway inflammation in atopic/allergic animals, including NC/Nga mice (which naturally develop an atopic dermatitis-like pathophysiology; Takano et al, 1997;Ichinose et al, 1998;Inoue et al, 2005a). Furthermore, DEP reportedly affect/disrupt several cell populations, which contributes to their immunotoxicity, such as epithelial cells (Terada et al, 1997;Takizawa et al, 2003), endothelial cells (Terada et al, 1999), macrophages (Beck-Speier et al, 2005), eosinophils (Hirota et al, 2008), dendritic cells (DC: Inoue et al, 2009), and mast cells/basophils (Saneyoshi et al, 1997;Devouassoux et al, 2002), mainly in vitro. Generally, peripheral lymphoid organs such as the spleen and their resident mononuclear cells including lymphocytes, are key players in the immunopathogenesis of allergy; thus, the effects of DEP on these compartments may provide much information on their adjuvant effects.…”
Section: Introductionsupporting
confidence: 86%
“…Consistent with this, we and others have previously demonstrated that DEP exposure induces and/or aggravates airway inflammation in atopic/allergic animals, including NC/Nga mice (which naturally develop an atopic dermatitis-like pathophysiology; Takano et al, 1997;Ichinose et al, 1998;Inoue et al, 2005a). Furthermore, DEP reportedly affect/disrupt several cell populations, which contributes to their immunotoxicity, such as epithelial cells (Terada et al, 1997;Takizawa et al, 2003), endothelial cells (Terada et al, 1999), macrophages (Beck-Speier et al, 2005), eosinophils (Hirota et al, 2008), dendritic cells (DC: Inoue et al, 2009), and mast cells/basophils (Saneyoshi et al, 1997;Devouassoux et al, 2002), mainly in vitro. Generally, peripheral lymphoid organs such as the spleen and their resident mononuclear cells including lymphocytes, are key players in the immunopathogenesis of allergy; thus, the effects of DEP on these compartments may provide much information on their adjuvant effects.…”
Section: Introductionsupporting
confidence: 86%
“…IL-8 is an important activator and chemoattractant for polymorphonuclear leukocytes and has been implicated in a variety of inflammatory diseases, such as asthma [41]. IL-8 protein is secreted at low levels from cells that have not been stimulated, but its production is rapidly induced by a wide range of stimuli encompassing proinflammatory cytokines [42], bacterial or viral products [43,44] and cellular stressors [45,46]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that exposure to diesel exhaust particles, PM 2.5 , and silica induced activation of NF-B in vitro and in vivo (Cho et al, 2003;Hirota et al, 2008;Shukla et al, 2000).…”
Section: Discussionmentioning
confidence: 99%